Diagnostic value of standard electrocardiogram in acute right ventricular myocardial infarction - Ali Taherinia; Koorosh Ahmadi; Mehran Bahramian; Peyman Khademhosseini; Zabihollah Taleshi; Mohammadreza Maghsoudi; Roya Sattarzadeh Badkoubeh; Mohammad Taghi Talebian; Mehdi Rezaee (PAGEPress Publications, 2019)
Myocardial infarction (MI) (i.e., heart attack) is the irreversible death (necrosis) of heart muscle secondary to prolonged lack of oxygen supply (ischemia) which accounts for a large number of deaths in the hospital. Diagnosis of myocardial infarction is confirmed based on clinical manifestations and electrocardiographic changes along with increased cardiac enzymes. Electrocardiogram (ECG) is one of the safest and easiest methods in the first place. Therefore, this study aimed to investigate the diagnostic value of standard electrocardiogram in the diagnosis of acute right ventricular infarction following lower cardiac infarction. This research was carried out at a time interval of one and a half years to diagnose acute primary infarction. In this method, the diagnostic value of ST↓ in lead I, ST↓ in lead aVL and I ST↓ + aVL, compared with ST↑ in lead V4R was investigated for diagnosis of right ventricular infarction. ST↑ in the lead V4R is a gold standard for the detection of right ventricular MI. All the patients who had the inclusion criteria were allowed to participate in the study. A total of 66 patients participated in the study. Accordingly, 58 (87%) were male and 8 (13%) were female. The mean age of the population was 54.9 ± 11.41. According to the ST↑ standard in lead V4R, 26 patients (39%) had right ventricular myocardial infarction. There was no significant relationship between angina pectoris and premature infarction (P-Value = 0.869). In this study, the right ventricular was most commonly involved in right coronary artery (RCA) (78%). There was no significant relationship between the occlusion of right coronary artery and right ventricular infarction in 60 patients (P-Value = 0.94). The results showed that electrocardiogram manifestations help determine the occlusion site and the area at risk (ST↓ in lead aVL and aVL + I, sensitivity = 96%). In myocardial infarction, symptoms such as the ST-Segment elevation in lead aVR and ST-Segment depression in the lower leads are possible. Accordingly, in the lower infarction, ST changes in the leads V1-V6 are helpful in detecting patients at risk. Thus, the use of electrocardiogram in acute myocardial infarction (AMI) helps detect more invasive patients and prevents extensive myocardial damage and other complications.